FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI PADA ANAK BALITA USIA 12-59 BULAN - Kamaruddin, Mustamir; Khodija, Unziya; Ramli, Kamrianti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Malnutrition among children under five is a serious issue in West Sumatra Province. According to the SSGI in 2022, underweight children in West Sumatra province reached 19.4%. The underweight cases by district / city are Pasaman District 24.8%, West Pasaman 23.8% and Sawahlunto 22.6%. The purpose of the study was to determine the factors associated with nutritional status in children under five years of age 12-59 months. The research design used in this study was cross sectional. The study was conducted in the Lubuk Buaya Health Center area. The research was conducted in September 2023. The study population was children under five (12-59 months) in the Lubuk Buaya Health Center work area which amounted to 264 toddlers. The sample amounted to 80 respondents. The sampling technique used Simple random sampling. Data analysis was done univariate and bivariate. The results showed there was a relationship between diet (p value: 0.017) and family income (p value: 0.010) on the nutritional status of toddlers. It is recommended that the Puskesmas and the person in charge of maternal and child health (MCH) can further increase the source of information for mothers of toddlers about the incidence of nutritional status in children and causative factors by conducting regular health counseling and by distributing leaflets or sticking posters at the health center about the importance of checking nutritional status in children under five years of age 12-59 months.Keywords: Toddlers, Nutrition, Income, Diet.